1997
DOI: 10.1111/j.1524-4725.1997.tb00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Malignant Melanoma Treated by Mohs Surgery Review of the Treatment Results of 179 Cases from the Mohs Melanoma Registry

Abstract: For thin and intermediate melanoma thicknesses treatment by either method appears to be equally efficacious. For deep melanomas, the number of cases were insufficient to evaluate. Further study of this high-risk category is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…Case series have supported the efficacy of Mohs surgery for MIS, with longterm cure rates equaling or exceeding historical cure rates with conventional wide local excision. [42][43][44] In our study, more than half of all respondents reported the use of Mohs micrographic surgery in the surgical treatment of facial MIS, whereas most respondents favored traditional surgical excision for nonfacial lesions. This differential practice in treating facial vs nonfacial MIS is likely due to the finding that recurrence rates on the head and neck are especially high after local excision.…”
Section: Mohs Micrographic Surgerymentioning
confidence: 83%
“…Case series have supported the efficacy of Mohs surgery for MIS, with longterm cure rates equaling or exceeding historical cure rates with conventional wide local excision. [42][43][44] In our study, more than half of all respondents reported the use of Mohs micrographic surgery in the surgical treatment of facial MIS, whereas most respondents favored traditional surgical excision for nonfacial lesions. This differential practice in treating facial vs nonfacial MIS is likely due to the finding that recurrence rates on the head and neck are especially high after local excision.…”
Section: Mohs Micrographic Surgerymentioning
confidence: 83%
“…Accurate interpretation involves considerable experience of the Mohs surgeon, and depends on high quality frozen section slides [6,14,28]. In frozen sections, the keratinocytes may appear vacuolated, resembling melanocytes, which may also be altered in the processing.…”
Section: Discussionmentioning
confidence: 99%
“…Margin controlled excision surgery using Mohs micrographic surgery (MMS) method carries the lowest recurrence rate (0-3%) of all the therapies [2,[5][6][7]. Drawbacks to MMS include the difficulty of histological diagnosis of frozen sections.…”
Section: Introductionmentioning
confidence: 99%
“…5,[8][9][10][11][12][13][14] Because of poorly defined clinical margins, unpredictable subclinical extension, and the head and neck location, margin-controlled surgical techniques such as staged excision with rush paraffin-embedded permanent sections and Mohs micrographic surgery have been proposed for the treatment of LM and LMM with low recurrence rates of 0.5% to 5%. [12][13][14][15][16][17][18] We report our experience with 117 LM and LMM cases excised with a staged technique and rush permanent sections. Our goal was to further define clinical and histologic features, assess frequency of unsuspected occult invasive melanoma, assess surgical margins required for complete excision, and report our approach with a margin-controlled excision technique.…”
mentioning
confidence: 99%